Natural Products: Perspectives and Challenges for use of Brazilian Plant Species in the Bioeconomy - Valli, Marilia [UNESP]; Bolzani, Vanderlan S. [UNESP] (FapUNIFESP (SciELO), 2019)
The development of our society has been based on the use of biodiversity, especially for nutrition, medicines and beauty. Brazil is the nation with the largest biodiversity in the world, with a rich chemical diversity, which is a potential source for bioeconomy. Considering the chemical and biological diversity of the Brazilian territory, we would like to highlight the value of secondary metabolites from Brazilian biodiversity with potential application for new products and technologies and the importance of scientific programs to support the sustainable use of biodiversity.